Utilization Analysis of the Ethyl Acetate Fraction of Cumin Leaves (Plectranthus amboinicus) as an Antimicrobial against Staphylococcus aureus using LC-MS - Rahma Diyan Martha; Ayu Insa Fajri; Danar Danar; Siti Nurriyatul Kholifah; Hesty Parbuntari (Department of Chemistry - Universitas Bangka Belitung, 2024)
The research investigates the antibacterial potential of cumin leaves due to their rich composition of flavonoid compounds, alkaloids, saponins, and tannins. The study's objectives encompass assessing the antibacterial efficacy of cumin leaf's ethyl acetate fraction against Staphylococcus aureus bacteria, identifying the concentration of this fraction yielding the most substantial inhibition zone, and characterizing the compound composition within the fractionated cumin leaf extract. Extraction involved maceration using 96% ethanol and fractionation through water, n-hexane, and ethyl acetate solvents. The ethyl acetate fraction's phytochemical screening affirmed the presence of flavonoids, alkaloids, saponins, and tannins. Liquid chromatography-mass spectrometer (LC-MS) analysis pinpointed the top two peaks as flavonoid compounds. Antibacterial assessments, executed via paper disc diffusion method, employed concentrations of 15%, 20%, and 25% of the ethyl acetate cumin leaf extract against Staphylococcus aureus, each repeated thrice. The 20% concentration exhibited the most substantial inhibition zone, averaging 23.1mm, compared to 16.8mm for 15% and 19.6mm for 25%, indicating its optimal efficacy against S. aureus growth. Statistical analysis employing ANOVA testing underscored the significance of the ethyl acetate cumin leaf fraction's concentration variations on S. aureus, as evidenced by a p-value of 0.00 (below the significance threshold of 0.05). This underscores the impact of the ethyl acetate cumin leaf fraction's concentrations on inhibiting S. aureus growth. The findings shed light on the potential of cumin leaves as a source of antimicrobial agents, with the 20% ethyl acetate fraction exhibiting notable effectiveness, opening avenues for further exploration and applications in antibacterial research.